Supply Chain Management Information System Analysis In Services Private Banks - Lutfi Alhazami; Alivia Rachmawati (International Journal of Management, Business, and Social Sciences, 2022)
This study aims to get a more specific understanding by describing the Supply chain management information system in the mobile banking application and understanding the effectiveness of the use of m-BCA as a form of information system. This type of research is descriptive quantitative by analyzing and identifying problems in finding the effectiveness of m-BCA information system. The data collection process in this study was carried out by conducting experiments using m-BCA which became the main source and other data sources taken from various media containing m-BCA report data. Based on the results of the data that researchers do refer to the 3 main functions of mobile banking, namely convenient, practical and easy. While the results of 300 mobile banking users 93.3% rated effective at the level of need and convenience. Then 10% less effective and 3.3% less effective users agree and disagree because the UI (User Interface) of mobile banking is less attractive. Finally, the security level can be assessed as effective with a percentage of 80% and less effective 20% because the application login security does not yet have a fingerprint and face id which he thinks is more secure and practical.